Photocatalytic activity of CuInS2 nanoparticles synthesized via a simple and rapid microwave heating process - Nawapong Chumha (2020)
© 2020 The Author(s). Published by IOP Publishing Ltd. In this research, visible-light photocatalytic activities of CuInS2 nanoparticles for degradation of three organic dyes (rhodamine B; RhB, methylene blue; MB, and methyl orange; MO) were investigated. The CuInS2 nanoparticles were synthesized by a simple and rapid microwave heating process using sodium sulfide as a sulfur source and then characterized by x-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET), and UV-vis diffuse reflectance spectroscopy (UV-vis DRS) techniques. The synthesized CuInS2 nanoparticles exhibited excellent photocatalytic degradation activity to the cationic dyes (RhB and MB) when compared with that of anionic dye (MO). Zeta potential of the CuInS2 photocatalyst was measured to elucidate the adsorption ability toward dye molecules. A possible photocatalytic degradation mechanism was proposed based on active species quenching experiments and Mott-Schottky analysis.